Extravesical robot‐assisted laparoscopic ureteral reimplantation for vesicoureteral reflux: Initial experience in Japan with the ureteral advancement technique. (20th May 2014) - Hayashi, Yutaro; Mizuno, Kentaro; Kurokawa, Satoshi; Nakane, Akihiro; Kamisawa, Hideyuki; Nishio, Hidenori; Moritoki, Yoshinobu; Tozawa, Keiichi; Kohri, Kenjiro; Kojima, Yoshiyuki
<x xml:space="preserve">Abstract</x> Objectives To report our initial experience with robot‐assisted laparoscopic extravesical ureteral reimplantation using the ureteral advancement technique. Methods A total of 15 ureters from nine patients (age range 2–25 years) underwent robot‐assisted laparoscopic extravesical ureteral reimplantation for the management of vesicoureteral reflux. The reflux was classified as grade I in one ureter, grade II in two ureters, grade III in seven ureters, grade IV in three ureters and grade V in two ureters. One of the five female patients had a bilateral duplex system, and reflux was observed in all four ureters. The da Vinci surgical system was utilized. Ureteral advancement was carried out in all cases. We also compared the operative outcomes between conventional laparoscopic procedure and robotic surgery. Results The console time was 211.5 ± 87.4 min (median ± standard deviation) in the bilateral cases and 144.0 ± 40.8 min in the unilateral cases. Urethral catheters were removed at one or two postoperative days. None of the patients suffered postoperative complications, such as urine leakage or urinary retention. Postoperative voiding cystourethrography showed that the reflux had been resolved in 14 of the 15 ureters (success rate 93.3%). In the remaining case, the reflux grade decreased from III to I. The operative outcomes of robotic surgery were favorable and safe compared with conventional laparoscopic procedure. Conclusions Our preliminary results showed that robot‐assisted laparoscopic surgery is a feasible and useful approach to extravesical ureteral reimplantation, even for patients with bilateral reflux.